Examination of the reliability of catch statistics in the Japanese coastal sperm whale fishery - Kasuya, Toshio (J. Cetacean Res. Manage., 1999)
Catch statistics are important for the assessment of whale stocks. The paper reviews earlier questions over the reliability of statistics from. the Japanese land based sperm whale fishery, and presents some new information for the periods 1959-65 and 1983-84, The available data suggest that aspects of post-World War I statistics are unreliable to an unknown extent in terms of total numbers, length and sex ratio. The evel of unreliahility appears to vary by month, year and whaling company. Suggestions for furure work to try to determine the likely levels of unreliability are presented. This is important to enable an accurate assessment of the status of North Pacific sperm whales.